The Stigma and Self-Stigma Scales for attitudes to mental health problems: Psychometric properties and its relationship to mental health problems and absenteeism. - Alys E. Docksey; Nicola S. Gray; Helen B. Davies; Nicola Simkiss; Robert J. Snowden (Health Psychology Research)
The Stigma and Self-Stigma scales (SASS) measure multiple aspects of stigmatic beliefs about mental health problems, including cognitive aspects of stigma towards others (Stigma to Others) and emotional stigma toward others (Social Distance), anticipated stigma by others, self-stigma, avoidant coping strategies, and help-seeking intentions, alongside an index of social desirability. The properties of the SASS were investigated by employees of a large UK government organization. With minor exceptions, each of the SASS scales had strong psychometric properties, good internal reliability, and test-retest reliability. Social Distance, Anticipated Stigma, Self-Stigma, and Avoidant Coping were all strongly associated with a lack of help-seeking for mental health problems. Similarly, Stigma to Others, Self-Stigma, and Avoidant Coping were all associated with current mental health problems. Finally, absenteeism from the workplace was found to be negatively related to Stigma to Others, and positively related to Avoidant Coping and Anticipated Stigma. In conclusion, the SASS was able to measure several different forms of stigma about mental health simultaneously in people both with and without a history of mental health problems. The SASS can be used to monitor changes in mental health attitudes outcomes following intervention programs to investigate stigmatic attitudes to mental health problems across different samples.